Placing Citizen Digital Competence in the Sustainable Development Goals: An Empirical Study in the Autonomous City of Ceuta - Tnibar-Harrus, Chaimae; Latorre Medina, María José (Cooperativismo & Desarrollo, 2024)
The Sustainable Development Goals stand as guiding principles of a Society of Information and Knowledge. Specifically, the objective of this study was to know the level of development of digital citizenship competence of teaching professionals trained at the Faculty of Education, Economy and Technology of the University of Granada in Ceuta (Spain). For this purpose, a methodological design of quantitative approach was carried out through an ad hoc questionnaire that has been validated by expert judgment technique. The results obtained from the descriptive analyses, which were subjected to statistical treatment, reveal that future teachers are very skilled in the five areas of the DigComp framework. This optimal level is accentuated in the skills of communication and collaboration, as well as in the creation of digital content. A comparison between graduating classes shows that this group of students is also considered to be particularly competent in the areas of security and digital pedagogy. However, the development of most skills is of common scope, among students and graduates, because of the theoretical and practical training that they have received at the Faculty. Undoubtedly, this is a pending research niche that must be explored from a multi, inter and transdisciplinary perspective.
Keywords: digital gap; sustainable development; Higher Education; social inclusion; Educational Technology